(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Religious tourism as a form of cultural tourism is becoming an increasingly powerful driver for socioeconomic progress, particularly in culturally diverse states like Western Maharashtra. This work attempts to capture the complex linkage between pilgrimage-oriented tourism and local area development by investigating the nature and extent of influence of religious tourism on regional economies, societal hierarchies, and the built environment at well-known centres of pilgrimage such as Shirdi, Pandharpur, Jejuri, and Kolhapur. Through a flux of local and foreign pilgrims, these locations have witnessed a wave of economic activity, such as hospitality services, transportation, handicrafts, and local enterprise, resulting in more jobs and income generation. This study assesses the role of religious tourism in poverty reduction, infrastructure development, and maintenance of cultural heritage, as well as the challenges like environmental degradation, congestion, and commodification of holy sites. The research methodology employed in the study is a mixed-methods approach that involves qualitative data collection through interviews, focus group discussions, field observations, as well as quantitative data collection using surveys and economic indicators. The study critically analyzes the roles of local governance, government policies, and community participation towards enabling sustainable tourism practices. It also explores the interaction between economic and religious motives, unearthing the extent to which religious feelings are interwoven with developmental aspirations across the region. The research provides evidence that religious tourism in Western Maharashtra has made substantial contributions towards regional development by enhancing infrastructure, creating employment opportunities, and fostering social integration. The gains are, however, unevenly shared and usually with accompanying socio-cultural tensions and environmental degradation. The research concludes on the basis of recommendations for an inclusive, sustainable, and people-centered model of tourism that honors the sanctity of pilgrimage centers while optimizing developmental impacts. These findings seek to guide policymakers, tourism planners, and local stakeholders on the strategic utilization of religious tourism for sustainable regional development.